Programa de educación ambiental para la gestión de residuos sólidos en la Institución Educativa Adventista “Emanuel” Gran Chimú-La Libertad - Castillo Silva, Shanik Neile (2021)
Today the generation of solid waste is one of the biggest problems in the country and one of the tools to become aware and develop positive habits in favor of our environment is environmental education, for which in this research work we have The objective of evaluating the Environmental Education Program for Solid Waste Management in the Adventist Educational Institution "Emanuel" Cascas, Gran Chimú Province, La Libertad 2019. For which we worked with primary level students (3rd, 4th, 5th, 6th ) and secondary level (1st, 2nd, 3rd, 4th), with a total of 49 students; It began by carrying out a pre-test to measure the level of environmental awareness in solid waste management, obtaining a coefficient of variation for the primary level; in the third grade with a CV = 28.43, fourth grade CV = 35.56, fifth grade CV = 35.56, sixth grade CV: 45.66, and for the secondary level, first year CV = 45.66, second year CV = 45.66, third year CV = 29.88, fourth year CV = 60.47, then training was carried out for a period of 4 months, which allowed the students to acquire a change in their knowledge and habits. Then a post-test evaluation (habits and knowledge) was taken to measure the level of environmental awareness reached, obtaining a coefficient of variation for the primary level; in the third grade with a CV = 17.8, fourth grade CV = 18.96, fifth grade CV = 12.66, sixth grade CV = 13.89 and for the secondary level, first year CV = 7.79, second year CV = 17.55, third year CV = 10.63 , fourth year CV = 16.49, demonstrating a positive variation in the level of environmental awareness after the environmental education program for solid waste management in the institution.